Treatment for benign thyroid nodules with a combination of natural extracts - Stancioiu, Felician (Mol Med Rep, 2019)
Benign thyroid nodules are among the most common endocrine disorders. Recent advances in diagnostic imaging and pathology have significantly contributed to better risk stratification of thyroid nodules. However, current treatment options, beyond surgical approaches are limited. The following placebo-controlled study presents, to the best of our knowledge, the first results of a non-invasive therapy for benign thyroid nodules. The efficacy and safety of a supplement containing spirulina, curcumin and Boswellia in euthyroid patients with benign thyroid nodules, was assessed by a 3 month, double-blind, placebo-controlled study which was completed by 34 patients. Patients with benign (FNAB documented) single thyroid nodules between 2 and 5 cm were evaluated in a prospective placebo-controlled cross-over trial, across 12 weeks (3 visits with six-week intervals). At each visit, the target thyroid nodule was recorded in two dimensions. In addition, plasma levels of thyroid stimulating hormone, free thyroxine and copper were assessed. The mean initial nodule area at V1 was 4.38±3.14 cm(2), at V2 3.87±2.79 cm(2), and at V3 3.53±2.84 cm(2); P<0.04. Administration of the active substances (n=34) was followed by a mean area decrease of 0.611 cm(2)±0.933 (SD), while placebo administration (n=29) was followed by a mean decrease of 0.178 cm(2)±0.515 (SD), (P=0.027). The presented findings suggest that the combination of spirulina-curcumin-Boswellia is effective in reducing the size of benign thyroid nodules. However, additional studies are needed in order to elucidate the exact mechanisms through which the suggested supplement facilitates a decrease in the size of benign thyroid nodules.